Diagnostic Accuracy of Blood-Based Biomarker Panels: A Systematic Review - Hardy-Sosa, Anette; León-Arcia, Karen; Llibre-Guerra, Jorge J.; Berlanga-Acosta, Jorge; Baez, Saiyet de la C.; Guillen-Nieto, Gerardo; Valdes-Sosa, Pedro A. (Frontiers in Aging Neuroscience, 2022)
Background: Due to the high prevalence of Alzheimer's disease (AD) in middle and low-income countries, there is an urgent need for inexpensive and minimally invasive diagnostic tests to detect biomarkers in the earliest and asymptomatic stages of the disease. Blood-based biomarkers biomarkers are predicted to have the most impact for use as a screening tool and predict the onset of AD. Methods: Medline/Pubmed was searched to identify current relevant studies published from January 2016 to December 2020. We included all full-text articles examining blood-based biomarkers, or set of protein markers, to aid in the early diagnosis, prognosis, and characterization of AD. Results: Sixty-six articles met the inclusion criteria to be included in the systematic review. The majority of studies reported biomarkers in plasma and serum. Conventional biomarkers amyloid-beta and tau, and neuroinflammatory biomarkers were the most represented, with amyloid beta-42, amyloid beta-40, total tau, phosphorylated tau-181, brain-derived neurotrophic factor, and complement C3 proposed in three or more studies. Protein-based biomarker panels were reported to aid in AD diagnosis and prognosis. We found amyloid beta-42/amyloid beta-40 ratio combined with APOEε4 status to be most represented with high accuracy for predicting amyloid beta-positron emission tomography status. In addition, complement C3 combined with A1-Microglobulin and A2-Macroglobulin reported high accuracy in panels for discriminating between AD and healthy individuals. Conclusions: The assessment of Alzheimer's disease biomarkers in blood as a noninvasive and cost-effective alternative will potentially contribute to the early diagnosis and improvement of therapeutic interventions. Given the heterogeneous nature of AD, a combination of markers seems to perform better for the diagnosis and prognosis of the disease than individual biomarkers.